Investigation of Peptide Toxin Diversity in Ribbon Worms (Nemertea) Using a Transcriptomic Approach - Anna E. Vlasenko; Vasiliy G. Kuznetsov; Timur Yu. Magarlamov (Toxins, 2022)
Nemertea is a phylum of nonsegmented worms (supraphylum: Spiralia), also known as ribbon worms. The members of this phylum contain various toxins, including peptide toxins. Here, we provide a transcriptomic analysis of peptide toxins in 14 nemertean species, including Cephalothrix cf. simula, which was sequenced in the current study. The summarized data show that the number of toxin transcripts in the studied nemerteans varied from 12 to 82. The most represented groups of toxins were enzymes and ion channel inhibitors, which, in total, reached a proportion of 72% in some species, and the least represented were pore-forming toxins and neurotoxins, the total proportion of which did not exceed 18%. The study revealed that nemerteans possess a much greater variety of toxins than previously thought and showed that these animals are a promising object for the investigation of venom diversity and evolution, and in the search for new peptide toxins.